A fluorination method for measuring the 13C‐13C isotopologue of C2 molecules. (14th April 2020) - Taguchi, Koudai; Yamamoto, Tomonari; Nakagawa, Mayuko; Gilbert, Alexis; Ueno, Yuichiro
Abstract : Rationale: Doubly substituted isotope species ("clumped" isotopes) can provide insights into the biogeochemical history of a molecule, including its temperature of formation and/or its (bio)synthetic pathway. Here, we propose a new fluorination method for the measurement of 13 C‐ 13 C species in C2 molecules using a conventional isotope ratio mass spectrometer. Target molecules include ethane, ethene and ethanol. Methods: 13 C‐ 13 C isotope species in C2 molecules were measured as C2 F6 using a conventional isotope ratio mass spectrometer. Ethane and ethene are directly fluorinated to C2 F6 . Ethanol is measured after dehydration to ethene and subsequent fluorination of the latter. The method enables the measurement of the Δ 13 C 13 C values normalized against a reference working standard. Results: The reproducibility of the whole protocol, including chemical modification steps and measurement of C2 F6 isotopologues, is better than ±0.14‰ for all the compounds. Ethane from natural gas samples and biologically derived ethanol show a narrow range of Δ 13 C 13 C values, varying from 0.72‰ to 0.90‰. In contrast, synthetic ethanol as well as putative abiotic ethane show Δ 13 C 13 C values significantly different from this range with values of 1.14‰ and 0.25‰, respectively. Conclusions: The method presented here provides alternative means of measuring 13 C‐ 13 C species to that using high‐resolution mass spectrometry. Preliminary data from natural and synthetic molecules re‐emphasizes the potential of 13 C clumped isotope species as a (bio)marker.